2021
DOI: 10.1021/acsenergylett.1c01007
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Cations’ Solvation on Charge Storage Performance in Polyimide Anodes for Aqueous Multivalent Ion Batteries

Abstract: Among the examined organic electrodes for aqueous mono and multivalent ions batteries, polyimide is considered a promising candidate because of its high capacity and good cyclability in different electrolyte solutions. While most of the studies so far were focused on the energetic performance of polyimide anodes, much less is known about their charge storage mechanism and particularly how such electrodes are affected by the solvation properties of the inserted cations. Using in situ EQCM-D, a direct assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…A low charge transfer resistance ( R p , 530 Ω) shows the cation transferability of the PI. [ 12 ] The additional charge transfer process due to the formation of the PI layer will impede ion diffusion in the electrode. Therefore, the solid diffusion coefficient (D) obtained from the galvanostatic intermittent titration technique (Figure S3, Supporting Information) shows that the D value of MnO 2 ‐PVDF is higher than that of MnO 2 ‐PI (Figure 2c).…”
Section: Resultsmentioning
confidence: 99%
“…A low charge transfer resistance ( R p , 530 Ω) shows the cation transferability of the PI. [ 12 ] The additional charge transfer process due to the formation of the PI layer will impede ion diffusion in the electrode. Therefore, the solid diffusion coefficient (D) obtained from the galvanostatic intermittent titration technique (Figure S3, Supporting Information) shows that the D value of MnO 2 ‐PVDF is higher than that of MnO 2 ‐PI (Figure 2c).…”
Section: Resultsmentioning
confidence: 99%
“…In order to separate the involvement of anions and the proton-dominated charge transfer in the charge-compensation process, the EQCM-D responses were measured only across the first and the second peaks (i.e., formation of ES + ·(A ins – ) and PPhz + ·(A ins – ), see Figure c,e). Similarly, EQCM-D measurements were performed separately across the third CV peak (shift of potential from 0.45 to 0.75 V) in which the deprotonation/protonation process of the PANI takes place, see Figure d,f …”
Section: Resultsmentioning
confidence: 99%
“…Similarly, EQCM-D measurements were performed separately across the third CV peak (shift of potential from 0.45 to 0.75 V) in which the deprotonation/protonation process of the PANI takes place, see Figure 3d,f. 23 Considering the amount of transferred charge, the theoretical frequency changes can be calculated by the following formula…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stagnation diffusion of massive and strongly bonded divalent charges such as Zn 2+ within MXene-based electrodes causes an issue in building high-performance ZHSC because of greater sizes and stronger electrostatic interactions of the divalent charges in comparison to the smaller, faster-moving, and smaller univalent charges. [229] A new design was proposed by Wu et al [230] which integrates well-behaved nanoscale spacers into a many-layered substrate via the homogenous intercalation of bacterial cellulose fiber (BCF) was created to overcome this issue to extend the interlayer spacing between restacked MXene sheets (MXene/BCF). Further, molecular dynamics simulation (MDS) and electrochemical testing found that by increasing the ion-transport channels of few-layered MXene sheets, Zn 2+ diffusion can be enhanced, thereby lowering the diffusion barrier for the MXene/BCF host electrodes.…”
Section: Mxenes-based Materialsmentioning
confidence: 99%